THE PERSPECTIVE OF INCREASING ENTRANCE FEES ONTOURIST DESTINATION FOR CONSERVATION OR MONOPOLI PURPOSE - Hariwanto, Army Tunggu (UI Scholars Hub, 2022)
As a big archipelago country Indonesia have many of tourist destination and attraction from east to west in whole over the archipelago. As much of its islands Indonesia have tourist destination which from nature give or even by human made. Tourist destination become one part that contain within one tour package that must visited by the tourist. Tourist must spend money to visit tourist destination and the cost will be different among them. From June until August there are few cases mentioned about increasing tourist destination entrance fees in several provinces and once become polemic among Indonesian citizen such entrance fee to Borobudur temple in Central Java and Komodo Island in East Nusa Tenggara. This polemic will become a bad image for Indonesia tourism views in foreigner and have multi flyer effect in economy and social life around tourist destination that already settled before.